Beginner's guide to zbrush - Lewis, Marisa; Lewis, Matthew (United Kingdom 3dtotalPublishing, 2017)
"Pixologic's ZBrush is the 3D world's premier digital sculpting software, widely used to create high-quality models for the video game, film, animation, and many other industries. Its uniquely intuitive approach to mideling makes it a fantastic asset for any creator hoping to realize their ideas in 3D. To usher students and 3D newcomers into comfortably using this powerful software. Beginner's guide to ZBrush presents a thorough introduction to the program with in-depth, accessible tutorials that will guide you through ZBrush's essential tools and techniques. Covering key concepts to help you get to grips with the principles of 3D, step-by-step organic, hard-surface, and mixed-surface sculpting workflows, and an overview of external rendering and 3D printing, this comprehensive volume will get you well on your way to creating your first exciting 3D projects from start to finish." -- Provided by publisher.
Introduction to ZBrush and 3D -- Introduction to the ZBrush interface -- Organic sculpting -- Mixed-surface sculpting -- Hard-surface sculpting -- Rendering with KeyShot -- Introduction to 3D printing
Includes index.
Keywords: Computer graphics